SERUM URIC ACID CONCENTRATION AND URINARY EXCRETION OF URIC ACID IN SUDANESE PATIENTS WITH GOUT - Khalid, Khalid E.; Ali, Khalid Eltom; Amir, Faisal Y. (Gezira Journal of Health Sciences, 2006)
Objectives: To assess the relationship between serum uric acid concentration and urinary excretion of uric acid in patients with gout. Materials and Methods: Fifty three Sudanese patients with gout were included in this study; thirty three of them were gouty subjects not under treatment, twenty subjects were under treatment. Twenty normal subjects were used as control. The biochemical parameters included in this study were: serum uric acid, urine uric acid. Urine volume, pH, specific gravity, and urine crystals were also determined. Results: Serum uric acid concentration in gouty subjects not under treatment was significantly higher (p<0.01) as compared to control group. While serum uric acid concentration in gouty subjects under treatment was not significantly higher than the control group, the difference between means was statistically significant between gouty subjects not under treatment and control group. No significant differences were found for urine uric acid excretion. There was a weak positive correlation between serum uric acid concentration and urinary excretion of uric acid in gouty groups; however control group gave a weak negative sign. The risk factors, which were considered, were obesity (over weight), ethnic origin, and age. The difference between means for body weight and height was significantly higher (P<0.05) in gouty subjects compared with control group, and the difference between means for urine volume, urine specific gravity, and urine crystalls showed no significant effect on the three groups, while urine pH showed significant mean difference between these groups. Conclusion: The determination of serum uric is of good diagnostic value, whereas estimation of urine uric acid is of little diagnostic value. Urine crystals can be used only for screening for the investigation of urine uric acid crystals.